REVIEW: CARACTERIZAÇÃO FÍSICA E FÍSICO-QUÍMICA DO FRUTO DE Bactris gasipaes (PUPUNHEIRA) E SUAS APLICAÇÕES TECNOLOGICAS (REMUNOM, 2024)
The peach palm (Bactris gasipaes Kunth) is a native plant found in greater abundance in the Amazon region. The peach palm fruit has different purposes, for the population that consumes it fresh or through the heart of palm and oil, extracted from the seed, with various purposes for trade. The fruit has a pleasant flavor and is rich in nutrients. From this, we sought to gather information from physical-chemical analyses, from several works already published, for subsequent comparison. In this sense, the objective of this study was to carry out a bibliographic survey regarding the physical and physicochemical characterization of the fruit of B. grasipaes, aiming at its application and contribution to future work. With the results; general aspects of peach palm, physical characterization of the fruit, characterization of fruit color, chemical characterization of fruit derivatives.